The impact of unconditional child cash grant on child malnutrition and its immediate and underlying causes in five districts of the Karnali Zone, Nepal – A trend analysis - Andre M. N. Renzaho; Wen Chen; Sanjay Rijal; Pradiumna Dahal; Ingrid R. Chikazaza; Thakur Dhakal; Stanley Chitekwe (Archives of Public Health, 2019)
Abstract Background The impact of unconditional cash transfers on child malnutrition and its determinants remains poorly understood. The aim of this study was evaluate the impact of an unconditional child cash grant on children’s nutritional status and its immediate (infant and young child feeding, dietary diversity, food consumption, and child infection and care) and underlying (household food security; Water, Hygiene and Sanitation (WASH) determinants among children younger than five years in the Karnali Zone, Nepal. Methods The five districts of the Karnali Zone received standard social welfare services in the form of targeted resource transfers for eligible families, plus an unconditional child cash payment, augmented by a capacity building and behavioural change education. Repeated cross-sectional surveys, with measures taken at baseline (2009, N=3750), midline (2013, N=3750) and endline (2015, N=3647), were carried out using a two-stage cluster sampling method. Multi-level Generalized Linear Mixed Models (GLMMs) with normal, binomial, Poisson, or multinomial link were performed to detect the unadjusted and adjusted trends. Results There was a linear growth among children, with a corresponding increase of 0.41 height-for-age Z-scores (p < 0.001), 0.50 weight-for-age Z-scores (p<0.001), and 0.34 weight-for-height Z-scores (p<0.001) between the study period, equating to a decline in child undernutrition of 9.4, 16.5, and 5.1 percentage points (p<0.001) for stunting, underweight, and wasting respectively. Improvements were also observed in WASH outcomes, care and health seeking behaviours, and food availability. Conclusion Unconditional child cash grant embedded within a government sponsored cash transfer program for families and complemented by capacity building and behavioural change strategies improves child nutritional status and its determinants.